A Kinetic and Mechanismic Study of Plasma-Induced Degradation of Monochloropropionic Acids in Water by Means of Anodic Contact Glow Discharge Electrolysis. (31st August 2016) - Yang, Haiming; Zhao, Xiaotong; An, Baigang; Li, Lixiang; Wang, Shaoyan; Ju, Maowei
Abstract : Decomposition of aqueous monochloropropionic acids (MCPAs) was investigated by means of anodic contact glow discharge electrolysis (CGDE). With the decay of MCPAs, the corresponding total organic carbon (TOC) also decreased smoothly. Furthermore, it was found that chlorine atoms in the MCPAs were released as chloride ions. As the main by-products, oxalic acid and formic acid were detected. The acetic acid (CA), monochloroacetic acid (MCA), and propanedioic acid (PDA) were also detected as the primary intermediates for decomposition of the corresponding MCPAs. The decay of both MCPAs and TOC obeyed the first-order kinetics, respectively. The apparent rate constant for the decay of MCPAs increased with the increase in p K a values of MCPAs, while that for the decay of TOC was substantially unaffected. The reaction pathway involving the successive attack of hydroxyl radical and the carbon chain cleavage were discussed based on the products and kinetics.